2007
DOI: 10.1086/509924
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Effects of Antibiotic Treatment on Duration of Symptoms Caused by Infection with Campylobacter Species

Abstract: Eleven randomized, controlled trials of antibiotic treatment versus placebo in patients with Campylobacter species infection were pooled in a meta-analysis. Antibiotic treatment shortened the duration of intestinal symptoms by 1.32 days (95% confidence interval, 0.64-1.99; P<.0001). Because of problems with drug resistance, a restrictive attitude towards the administration of antibiotics in uncomplicated cases is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 21 publications
7
65
0
6
Order By: Relevance
“…This bacterium may also cause bacteremia (1). Such enteric infections need to be treated with an antimicrobial agent in less than 50% of cases (2,6,15). Macrolides and fluoroquinolones are first-and second-choice antimicrobials for that purpose (2,4,5,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This bacterium may also cause bacteremia (1). Such enteric infections need to be treated with an antimicrobial agent in less than 50% of cases (2,6,15). Macrolides and fluoroquinolones are first-and second-choice antimicrobials for that purpose (2,4,5,6).…”
mentioning
confidence: 99%
“…Resistance of C. coli to fluoroquinolones is increasing over time, with the actual resistance rate at 30.8% in the United States (7). Routine susceptibility testing of C. coli has become a very important tool for appropriate antimicrobial treatment when needed (2,(6)(7)(8)(9)(10)(11)(14)(15)(16). The main erythromycin resistance mechanism of C. coli strains (mutation of 23S ribosomal rRNA and proteins) confers high-level resistance (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antibiotics for the treatment of Campylobacter infections is generally reserved for patients with moderate or severe disease (dehydrating diarrhea, dysentery), signs of systemic infection (fever, prostration) or underlying immunodeficiency (42). The antimicrobial therapy recommended for C. jejuni infection includes a macrolide antibiotic (i.e., azithromycin or erythromycin) for 3 days, as was initially done for our case subject (20).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, in Campylobacter infections, a study published in 1982 showed that antibiotics must be given within four days after symptom onset, 21 and a recent meta-analysis showed that antibiotic treatment shortened the duration of symptoms by only 1.3 days. 22 Although treatment of Salmonella carries with it an in creased risk of chronic carriage, bacteremia can occur in 2%-4% of patients. 4 Therefore, treatment should be considered in individuals with a positive culture result and who are at risk of serious infection or complications of bacteremia (Box 2).…”
Section: Pathogen-directed Treatmentmentioning
confidence: 99%